Republic of Belarus : Financial Sector Assessment Program; Detailed Assessment of Observance of CPSS Core Principles for Systemically Important Payment Systems; Belarus Interbank Settlement System; BISS; RTGS Service. (IMF Staff Country Reports; Country Report ;, 2006)
This Detailed Assessment of the Observance of Core Principles for Systemically Important Payment Systems (CPSS), Belarus Interbank Settlement System (BISS): RTGS Service on the Republic of Belarus reviews the core principles for systematically important payment systems. BISS offers the possibility to reserve funds in view of being used for certain specific purposes. Financial market activities in Belarusian rubel are limited, but potentially emerging. Although the Belarus Bankers Association in principle provides a forum for cooperation between banks, in payment system issues, it currently does not play an important role.